Utilization of Bagasse Waste Briquettes As An Alternative to Environmentally Friendly Technology - Fitriana, Febi; Wardana, Rendy Wikrama; Uliyandari, Mellyta; Sutarno, Sutarno; Saprudin, Saprudin (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
Briquettes represent environmentally sustainable solid fuels that utilize renewable resources. This study aimed to assess the quality of bagasse waste briquettes as an alternative in eco-friendly technology. The experimental method was conducted internally at the PT SUCOFINDO Bengkulu laboratory. Briquettes were produced using varying compositions of bagasse waste: A1 (80 grams charcoal flour and 12 grams tapioca flour), A2 (30 grams charcoal flour and 6 grams tapioca flour), and A3 (20 grams charcoal flour and 5 grams tapioca flour). The production process involved preparation, drying, monitoring, grinding, adhesive mixing, molding, and final drying. Quantitative data analysis focused on key parameters including water content, ash content, and calorific value. Results indicated that the briquettes with 80% charcoal flour and 20% tapioca flour exhibited the highest calorific value at 6155 kcal/kg. It was concluded that all types of bagasse waste briquettes met Indonesian National Standards, demonstrating their potential as an alternative energy source through environmentally friendly briquette technology.